Assessment of listing and categorisation of animal diseases within the framework of the Animal Health Law (Regulation (EU) No 2016/429): infestation with Varroa spp. (varroosis). (6th October 2017) - ,; More, Simon; Bøtner, Anette; Butterworth, Andrew; Calistri, Paolo; Depner, Klaus; Edwards, Sandra; Garin‐Bastuji, Bruno; Good, Margaret; Gortázar Schmidt, Christian; Michel, Virginie; Miranda, Miguel Angel; et al.
Abstract: Infestation with Varroa spp. (varroosis) has been assessed according to the criteria of the Animal Health Law (AHL), in particular criteria of Article 7 on disease profile and impacts, Article 5 on the eligibility of varroosis to be listed, Article 9 for the categorisation of varroosis according to disease prevention and control rules as in Annex IV and Article 8 on the list of animal species related to varroosis. The assessment has been performed following a methodology composed of information collection and compilation, expert judgement on each criterion at individual and, if no consensus was reached before, also at collective level. The output is composed of the categorical answer, and for the questions where no consensus was reached, the different supporting views are reported. Details on the methodology used for this assessment are explained in a separate opinion. According to the assessment performed, it is inconclusive whether varroosis can be considered eligible to be listed for Union intervention as laid down in Article 5(3) of the AHL because there was no full consensus on the criterion 5 A(v). Consequently, the assessment on compliance of varroosis with the criteria as in Annex IV to the AHL, for the application of the disease prevention and control rules referred to in Article 9(1), and which animal species can be considered to be listed for varroosis according to Article 8(3) are also inconclusive.